Pertussis in Italy: maternal immunization to protect infants. (30th September 2020) - Fiasca, F; Necozione, S; Mattei, A
Abstract: Background: Despite effective pertussis vaccines and high rates of pediatric vaccination in Italy, the number of reported pertussis cases has steadily increased. To minimize severe illness and deaths, particularly in infants, in addition to active immunization, maternal vaccination has been nationally recommended. To support this prevention measure, this study sought to gain more insight into the current pertussis burden among hospitalized infants. Methods: A retrospective observational study investigating infant hospitalizations for pertussis within the first year of life from 2007 to 2018 in Italy was carried out using the Hospital Discharge Database as informational flow. Four age groups were analyzed (<3, 3-4, 5-10, and 11-12 months), according to the expected age for the dose administration of the primary course of pertussis vaccination. The temporal trend of hospitalization rates was analyzed by the slope of the regression line. p < 0.05 was the criterion for statistical significance. Results: There were 4262 pertussis-related admissions among infants less than 12 months of age. Overall, 61.10% were infants aged <3 months. The overall hospitalization rate was 69 x 100000 infants. When stratified by age, infants <3 months old had the highest hospitalization rate at 169 x 100000 infants, with an increasing trend (β = 9.12, p = 0.002); for the other age groups, the trend increased less strongly or was substantially stable. Conclusions: This nationwide study highlighted that most of the pertussis admissions in Italy occurred in the first few months of life, before infants had started the primary vaccination course. This result indicates that more needs to be done to protect young infants (<3 months) who are the most vulnerable to severe disease. The implementation of maternal immunization programs could offer the hope of much better pertussis control in infants too young to be vaccinated. Key messages: Infants aged <3 months showed the highest rates of hospitalization for pertussis, with an increasing trend. The implementation of maternal immunization programs could protect these high-risk infants.